分解因式:(2x+1)(x-1)-(x+1)(x-2)-10
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 19:35:27
分解因式:(2x+1)(x-1)-(x+1)(x-2)-10分解因式:(2x+1)(x-1)-(x+1)(x-2)-10分解因式:(2x+1)(x-1)-(x+1)(x-2)-10(2x+1)(x-1
分解因式:(2x+1)(x-1)-(x+1)(x-2)-10
分解因式:(2x+1)(x-1)-(x+1)(x-2)-10
分解因式:(2x+1)(x-1)-(x+1)(x-2)-10
(2x+1)(x-1)-(x+1)(x-2)-10
=2x²-x-1-(x²-x-2)-10
=x²-9
=(x+3)(x-3)
原式=2X^2+X-2X-1-X^2-X+2X+2-10
=X^2-9
=(X+3)(X-3)
分解因式----(X*X-X)(X*X-X-2)+1
分解因式x²-2x+1
分解因式-x²-1+2x
分解因式x^4-x^2+1
x^2-23x+1分解因式
x^2-23x+1分解因式,
x^2-23x+1分解因式
x^2-23x+1分解因式,
分解因式x(x-2)(x+3)(x+1)+8,
分解因式:x(x-1)(x+2)(x+3)-40
x^2006-1分解因式
分解因式 x^7-1
分解因式:(x-1)(x-2)^2-(x-1)^3
分解因式:1/4x+x^3-x^2
分解因式:-x^3+ x^2-1/4x
分解因式:x^2(x+1)-y(xy+x)
x(x-1)(x-2)-6十字相乘分解因式
分解因式x^n-x^(n-1)+x^(n-2)